EFEKTIVITAS PROGRAM KERJA LITERASI KAMPUS MENGAJAR PADA ASESMEN KOMPETENSI MINIMUM (AKM) SISWA KELAS VIII DI SMP MUHAMMADIYAH 11 JAKARTA - Rahmawati, Ika; Jupri, Abdul Rahman (Dharmas Education Journal (DE_Journal), 2024)
Low reading literacy among students who are less exposed to reading culture, teaching campuses are present in the independent campus learning program (MBKM). This research aims to evaluate and describe the effectiveness of the Reading Corner and Library Revitalization literacy work program carried out by teaching campus students during the Minimum Competency Assessment (AKM) at SMP Muhammadiyah 11 Jakarta. The method used in this research is a qualitative approach. The data source is class VIII students at SMP Muhammadiyah 11 Jakarta. Data collection techniques in research use questionnaires, interviews and documentation. The results of this research are that the campus teaching literacy program at SMP Muhammadiyah 11 Jakarta has been effective. However, there are encouraging and inhibiting factors when implementing the MBKM teaching campus internship program, namely the lack of infrastructure in schools which causes the program to run less than optimally. Therefore, there needs to be continuous efforts in developing and empowering literacy which must be supported by schools in order to improve students' literacy skills.